Empowering Local Communities through Tourism Entrepreneurship: The Case of Micro Tourism Entrepreneurs in Langkawi Island - Nordin, Aleff Omar Shah; Tuan Lonik, Ku Azam; Jaafar, Mastura (EDP Sciences, 2014)
The tourism sector has a huge effect in developing countries by providing immense economic opportunities to the local community. Entrepreneurship has been identified as essential actors for creating job opportunities, generating income, increasing standard of living and generally growing the economy. Using the random sampling approach, the questionnaires were distributed to the tourism entrepreneurs in the tourism attraction area in Langkawi Island. During the survey period, only a total of 263 entrepreneurs completed the questionnaires. The objective of this study is to explore the economic empowerment of the tourism entrepreneurship in contributing to income level, creating job opportunities and increasing standard of living. The findings of the study clearly show that the tourism entrepreneur activities contribute positively to income level, jobs, opportunities and standard of living of the local community.